The Value of Orientation and Mobility in the Preparation, Response, and Recovery of the 2017 Hurricane Season in Puerto Rico. (September 2021) - McCormack, Kevin
Introduction: The 2017 hurricanes Irma and Maria significantly affected all people in Puerto Rico, including people with visual impairments. This population has historically been underserved; therefore, access to disaster-related services and the overall availability of training in independence skills are inadequate. This study focuses on independence as related to orientation and mobility (O&M) and was part of a larger case study that sought to determine what unique factors affected people with visual impairments during the aforementioned hurricanes and how challenges could potentially improve.Methods: Qualitative exploratory single-case study of the 2017 hurricane season in Puerto Rico. Interviews used language interpreters and were conducted in-person and by telephone between November 2 and December 17, 2018. Referred sampling included 29 people with visual impairments, four relief agencies, an Americans with Disabilities Act (ADA) technical specialist, and seven organizations serving people with visual impairments.Results: The post-Maria travel environment presented many challenges through altered infrastructure. Impact was also felt due to insufficient disaster-related institutional supports and a lack of empowerment for people with visual impairments. Post-disaster life presented mental health challenges; however, the usage of O&M training helped to curb its effects. For study participants, the greater the acquisition and practice of O&M, the greater their well-being.Discussion: Paternalism minimized the acquisition and practice of O&M. Knowledge and practice of O&M were salient in post-disaster life. The use of O&M aided in mental health before, during, and after the hurricanes.Implications for practitioners: Expressions of the importance of O&M skills among participants can be used to encourage future recipients of O&M training. These testimonials can also be used to advocate for more social support and financial assistance for organizations which provide such training.